The role of IT governance in the evolution of organizations in the digital economy: cases in Australian higher education - Bhattacharjya, Jyotirmoyee; Chang, Vanessa (IEEE, 2007)
In recent years, IT governance has become a key concern issue for senior IT decision makers across various industries. When appropriately implemented, IT governance can play the role of a central nervous system effectively ensuring the wellbeing of the organizational system. The health of the organizational system ultimately contributes to the health of the distributed business ecosystem in which the organization co-exists with other organizations. The underlying goals for adopting formal IT governance practices are improvement of business performance and conformance with regulations. This exploratory study examined how IT governance is implemented in four Australian institutions of higher education through a number of IT governance structures, processes, and relational mechanisms. This paper discusses the importance of these practices as these institutions increasingly compete and collaborate with each other, various government agencies and other research institutions in the digital economy.